2008
DOI: 10.1534/genetics.106.067603
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Mismatch Repair of Heteroduplexes Reveals “Non”-interfering Crossing Over in Wild-Type Saccharomyces cerevisiae

Abstract: Using small palindromes to monitor meiotic double-strand-break-repair (DSBr) events, we demonstrate that two distinct classes of crossovers occur during meiosis in wild-type yeast. We found that crossovers accompanying 5:3 segregation of a palindrome show no conventional (i.e., positive) interference, while crossovers with 6:2 or normal 4:4 segregation for the same palindrome, in the same cross, do manifest interference. Our observations support the concept of a ''non''-interference class and an interference c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
61
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(66 citation statements)
references
References 66 publications
5
61
0
Order By: Relevance
“…Indeed, one already knows that double-strand breaks mature into crossovers or into noncrossovers in proportions depending on the locus (Mancera et al 2008); such a propensity may extend to the choice of using one CO pathway rather than the other. Differences in the treatment of double-strand breaks may in fact tie in with the different mechanisms that are used for mis-match repair in the two pathways of CO formation (Getz et al 2008).…”
Section: P2-associated Hot Regions Within Chromosomesmentioning
confidence: 99%
“…Indeed, one already knows that double-strand breaks mature into crossovers or into noncrossovers in proportions depending on the locus (Mancera et al 2008); such a propensity may extend to the choice of using one CO pathway rather than the other. Differences in the treatment of double-strand breaks may in fact tie in with the different mechanisms that are used for mis-match repair in the two pathways of CO formation (Getz et al 2008).…”
Section: P2-associated Hot Regions Within Chromosomesmentioning
confidence: 99%
“…My genetic studies with T4, 7,8 were complemented by a bit of kibitzing, 9 followed by studies with Lambda 10,12 and then with yeast. [13][14][15][16][17] Throughout, I had the privilege of teaching courses in genetics and the pleasure of deeply rewarding sabbatical leaves in Cambridge UK (with Sidney Brenner and Francis Crick), 18 Edinburgh (with Noreen and Ken Murray), Jerusalem (with Giora Simchen), and Cambridge MA (with Maury Fox and David Botstein). Teaching lab courses in bacteriophage (Cold Spring Harbor, Naples and Bombay) sometimes started me smoking again.…”
mentioning
confidence: 99%
“…Zalevsky et al (1999) proposed that these crossovers represent a class of crossovers in wild-type yeast that serve to promote chromosome pairing. That proposal has received its most direct support from the observation of a class of crossovers in wild-type yeast, identifiable by their frequent evasion of mismatch repair, that lack positive interference and have a frequency that is independent of Msh4 (Getz et al 2008).…”
mentioning
confidence: 99%
“…Because the two-pathway interpretation restricts interference to the disjunction phase [ignoring the possibility of negative interference between interfering and noninterfering crossovers (Getz et al 2008)], the observed frequency of double crossovers becomes…”
mentioning
confidence: 99%
See 1 more Smart Citation